High Selectivity Towards Formate Production by Electrochemical Reduction of Carbon Dioxide at Copper–Bismuth Dendrites. Issue 1 (9th November 2018) - Hoffman, Zachary B.; Gray, Tristan S.; Xu, Yin; Lin, Qiyuan; Gunnoe, T. Brent; Zangari, Giovanni
Abstract: The electrochemical reduction of CO2 provides an alternative carbon‐neutral path for renewable synthesis of fuels and value‐added chemicals. This work demonstrates that dendritic, bimetallic Cu–Bi electrocatalysts with nanometer‐sized grains are capable of formate generation with a high selectivity. Optimizing composition of electrocatalyst could achieve a faradic efficiency of 90 % at −0.8 to −0.9 VRHE, and a partial current of more than 2 mA cm −2 . The combination of Cu with Bi enables modulation of the adsorption strength of intermediates. This leads to an increased selectivity and suppressed formation of spurious species, especially hydrogen and CO. Comparison of product distribution for Cu–In versus Cu–Bi indicated that Bi is essential to induce a favorable adsorption configuration of the intermediate species and to promote formate production. Abstract : Getting CO2 in format(e)ion : Cu–Bi bimetallic electrocatalysts for reduction of gaseous CO2 are synthesized by using electrodeposition. The efficiency, current density, and product selectivity of the catalysts are highly dependent on the composition and applied reduction potential. Optimized incorporation of Bi in Cu can achieve >90 % faradaic efficiency for formate production with a high product selectivity.